COMPARATIVE STUDY ON HIGH-PERFORMANCE THIN LAYER CHROMATOGRAPHY PROFILE AND ANTIMICROBIAL ACTIVITY OF ETHANOLIC AND HYDROALCOHOLIC EXTRACT OF VETIVERIA ZIZANIOIDES L. ROOT - Sivagurunathan, Saravana Kumar; Krishnamoorthy, Gayathri (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Scientific evaluation of traditionally using medicinal herbs for their pharmacological activity is a leading and valuable area of research. The aim of this study is to compare the antimicrobial activity of ethanolic and hydroalcoholic extract of Vetiveria zizanioides root and analyze the major bioactive compounds present in those extracts. Methods: Antimicrobial activity of both ethanolic and hydroalcoholic extracts was carried out against various pathogens such as Staphylococcus aureus, methicillin-resistant S. aureus (MRSA), Pseudomonas aeruginosa, and Candida albicans. A number of active compounds present in both extracts were compared by developing different compounds of the sample in high-performance thin layer chromatography (HPTLC) stationary phase using mobile phase petroleum ether:ethyl acetate:toluene:formic acid (5:5:1:1). Results: Ethanolic extract acts against pathogens such as S. aureus and MRSA, significantly (p<0.05) potent than that of hydroalcoholic extract. Significant difference has not been observed between ethanolic and hydroalcoholic extract when acts against P. aeruginosa and C. albicans. HPTLC profile of hydroalcoholic and ethanolic extract shows the presence of 10 and 14 different compounds, respectively, when developed with the same mobile phase. Gallic acid, a phenolic compound, was found to be present with higher % peak area in hydroalcoholic extract (3.25%) against ethanolic extract (2.98%). Conclusion: The results of this study reveal that zone of inhibition exhibited by both ethanolic and hydroalcoholic extracts was found to be different with dissimilar pathogens. A more number of compounds were eluted from hydroalcoholic extract than ethanolic extract. Â